Is there an Environmental Kuznets Inverted-U Shaped Curve? - Kiliç, Cüneyt; Balan, Feyza (Panoeconomicus, 2018)
This study examines the relationship among carbon dioxide (CO2) emissions, income, energy consumption, trade openness, financial development and institutional quality based on the environmental Kuznets curve (EKC) hypothesis in 151 countries for the period 1996-2010, using the Pooled Ordinary Least Squares methods. The results support cubic specification of the EKC hypothesis, which assumes a cubic polynomial inverted U-shaped relationship between income and environmental degradation. Other empirical results indicate that energy consumption, trade openness, financial development and institutional quality are significant variables in explaining CO2 emissions. Key words: CO2 emissions, Environmental Kuznets curve, Economic growth, Panel data analysis, Inverted U-Shape. JEL: C33, F18, F43. U radu se istražuje odnos između emisije ugljenog dioksida (CO2), prihoda, potrošnje energije, otvorenosti trgovine, finansijskog razvoja i institucionalnog kvaliteta zasnovanog na hipotezi Kuznetsove krive (EKC) u 151 zemlji za period 1996-2010. godine, koristeći metod objedinjenih običnih najmanjih kvadrata. Rezultati podržavaju kubičnu specifikaciju EKC hipoteze, koja pretpostavlja inverznu-U vezu karakterističnu za kubni polinomni odnos između prihoda i degradacije životne sredine. Drugi empirijski rezultati ukazuju na to da su potrošnja energije, otvorenost trgovine, finansijski razvoj i institucionalni kvalitet značajne varijable u objašnjavanju emisije CO2. Ključne reči: emisije CO2, Kuznetsova kriva životne sredine, ekonomski rast, analiza panelnih podataka, Inverzni-U oblik.